Phlebotominae fauna (Diptera: Psychodidae) in the department of Amazonas, Colombia (2003)
ABSTRACT: During the execution of an epidemiological study to assess the risk of Leishmania infection, an entomological evaluation and an inventory of phlebotomine fauna was made. The captures of phlebotomines were carried out with Shannon type traps and aspirators which collected the sand flies on human bait, in the Tikuna native community, on the banks of the Pupuña River an affluent of the Putumayo River among the department of Amazon. Five hundred and sixty phlebotomine specimens belonging to 20 species were captured in this place and the presence of Lutzomyia reducta Feliciangeli, Ramirez-Pérez & Ramirez recorded in Colombia for the first time and Lutzomyia carrerai carrerai (Barreto) and Lutzomyia nocticola Young were identified as new records for the zone. An updated inventory of phlebotomine species in Amazon department of Colombia is included.